2015
DOI: 10.1007/s00381-015-2786-3
|View full text |Cite
|
Sign up to set email alerts
|

The whole spectrum of cystic periventricular leukomalacia of the preterm infant: results from a large consecutive case series

Abstract: Long-term neurodevelopmental outcome of bilateral PVL always was adverse and different from unilateral PVL. The latter might be negatively influenced by associated intra- and periventricular haemorrhages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
1
24
1
3
Order By: Relevance
“…Although cPVL and IVH have high association and both contribute to increased risk of CP and cognitive impairment [4,10], few studies have reported neurodevelopmental outcomes of cPVL-affected infants with or without IVH. A previous study investigating IVH and developmental outcomes showed that extremely preterm infants with IVH and white matter lesions did not have increased risk of neurodevelopmental impairment than those with white matter lesions alone [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although cPVL and IVH have high association and both contribute to increased risk of CP and cognitive impairment [4,10], few studies have reported neurodevelopmental outcomes of cPVL-affected infants with or without IVH. A previous study investigating IVH and developmental outcomes showed that extremely preterm infants with IVH and white matter lesions did not have increased risk of neurodevelopmental impairment than those with white matter lesions alone [25].…”
Section: Discussionmentioning
confidence: 99%
“…Because cPVL may not develop until 3-6 weeks after birth [2,4], infants with complete ultrasound data (serial ultrasound scans recorded during the first 2 months of life until discharge) were included for analysis. Infants who died before 28 days after birth or did not receive complete ultrasound examinations were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, clinical studies focused on the association of risk for periventricular leukomalacia in PPROM exposed very preterm neonates: PPROM especially before 20-22 weeks of gestation is clearly associated with an increased risk for periventricular lesions as an independent factor apart from the degree of prematurity [6,8]. Longterm follow up of preterm neonates suffering from periventricular leukomalacia following among others PPROM confirm the serious consequences with respect neurodevelopmental impairments: cerebral palsy in 84 % and mental retardation in about 50 % was described in a large cohort from an Austrian singlecenter study using strictly defined neonatal and follow-up variables [10].…”
mentioning
confidence: 87%
“…There is evidence to suggest an inverse relationship between the degree of impairment and the gestational age at birth. An estimated 3% of infants born before 32 weeks of gestation have visual impairment, with an incidence of 53% in those with known PVL . Bilateral isolated hearing loss is reported at 2–3 years of age in 2.2% of children born before 28 weeks of gestation .…”
Section: The Link Between Preterm Birth and Perinatal Fetal Brain Injurymentioning
confidence: 99%